Progress on Polymer Dielectrics for Electrostatic Capacitors Application. Issue 29 (18th August 2022) - Luo, Hang; Wang, Fan; Guo, Ru; Zhang, Dou; He, Guanghu; Chen, Sheng; Wang, Qing
Abstract: Polymer dielectrics are attracting increasing attention for electrical energy storage owing to their advantages of mechanical flexibility, corrosion resistance, facile processability, light weight, great reliability, and high operating voltages. However, the dielectric constants of most dielectric polymers are less than 10, which results in low energy densities and limits their applications in electrostatic capacitors for advanced electronics and electrical power systems. Therefore, intensive efforts have been placed on the development of high‐energy‐density polymer dielectrics. In this perspective, the most recent results on the all‐organic polymer dielectrics are summarized, including molecular structure design, polymer blends, and layered structured polymers. The challenges in the field and suggestions for future research on high‐energy‐density polymer dielectrics are also presented. Abstract : The uniqueness of the review is mainly focused on all‐organic polymer dielectrics and aims to cover the molecular engineering strategies, including increased relatively permittivity, suppressed dielectric loss, enhanced breakdown strength, improved processability, and high‐temperature stability, in all‐organic polymer dielectric.